A review on bioactive compounds isolated from plants active against phytopathogenic fungi. - Yazdani, Darab; Tan, Yee How; Mior Ahmad, Zainal Abidin; Jaganath, I. B. (Academic Journals, 2011)
Plant-derived compounds are regarded as a substantial source for novel lead structures to develop medicines and biocides natural products. Concurrent with greater awareness towards the use of synthetic chemicals in agricultural practice, the application of integrated pest management programs has also increased. In recent years, there has been considerable public pressure to reduce the use of synthetic fungicides in agriculture. Although, the use of synthetic fungicides in plant disease control has been successful in improving agricultural output, several of these have been found to exhibit side-effects in the form of carcinogenicity, detrimental effects and other residual toxicities. The alternative choice therefore would be the use of botanical fungicides, which are found to be largely non-phytotoxic, systematic and easily biodegradable in nature. The present study is a summary of review literature during past decades which focused on bioactive compounds isolated from plants against plant pathogenic fungi.